Model IMC dalam Bisnis Pendidikan Vokasi di Politeknik Caltex Riau untuk Menguatkan Brand Positioning - Edi Tri Prayitno; Yozani, Ringgo Eldapi; Rumyeni (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pembangunan Nasional Veteran Jakarta, 2024)
Brand positioning is an effort to position the perception of a brand for consumers. The strength of brand positioning has the power to drive consumers to provide more value than competitors, which can be supported by the Integrated Marketing Communication (IMC) model. This research is based on efforts to improve and strengthen the brand positioning held by Polytechnic Caltex Riau. This is supported by the achievement of student admissions to Polytechnic Caltex Riau, which has shown a positive trend over the past five years amidst intense competition among vocational higher education institutions. This study explores how the IMC implemented by Polytechnic Caltex Riau can help strengthen brand positioning. The research method used in this study is qualitative, with data collection conducted directly and indirectly, and the sample selection technique is purposive sampling. The results of the research analysis found that the Integrated Marketing Communication of Polytechnic Caltex Riau is divided into two categories: the high category (Sales Promotion, Advertising, Sponsorship, Exhibitions, Merchandising, Social media, and Website) and the low category (Direct Marketing, Public Relations, Packaging, and Selling and Sales Management). The implementation process of marketing communication activities at Polytechnic Caltex Riau has seven layers of marketing tools, which the researcher refers to as the wafer layer marketing communication model. It is hoped that the IMC model used by Polytechnic Caltex Riau, which has seven stages in marketing communication activities including the Report, student admission announcement, Socialization, Follow Up, Engagement Program, Workshop, and Goes to School Program, can be used by other campuses to strengthen the brand positioning of vocational higher education institutions.